Prevalence of the pattern of Pre-labor premature rupture of membranes among pregnant women at Al-Sadaqa Teaching Hospital, Aden, Yemen - Al-Kaaky, Nahla Saleh (Journal of medical and pharmaceutical sciences, 2022)
Pre-labor rupture of membranes (PROM) is the rupture of membranes before the onset of labor. It is a common obstetric problem (3 -4%) in developed and developing countries. The aim of this study to describe the pattern of PROM in pregnancies at Al-Sadaqa Teaching Hospital, Aden, Yemen from January to February 2020. This is a descriptive hospital based study of the patients diagnosed as PROMs managed in the Obstetrics and Gynecology Department. In this study 151 pregnant women with PROM comprising 11.1% of 1360 total deliveries. Only 9 (0.7%) patients presented with preterm premature rupture of membranes (PPROM) and 142 (10.4%) with term premature rupture of membranes (TPROM). The mean maternal age with PROM was 26.12 ± 6.67 years. With increasing parity, there was a decrease in the PROM; 6.0% in multipara to 4.6% in grand-multipara. The time interval from membrane rupture to delivery was >24 hours in 47% of them. Anemia was the main predisposing factor causing PROMs (47.0%) followed by history of abortion and urinary tract infection (UTI) (29.1%, and 19.9% respectively). About 81.5% of them delivered vaginally while 18.5% by lower segment cesarean section. Conclusions: The prevalence of PROM in this study was comparably higher than the international average. A higher proportion of them delivered vaginally. The major contributing factors were anemia, history of abortion and UTI and increasing risk with prolonged rupture of membrane > 24hrs. It is of paramount importance to screen for UTI with timely treatment initiation and those with recurrent abortion require close monitoring on risk of PROM during subsequent pregnancies.